Effects of frustration on the nonequilibrium dynamics of photoexcited lattice systems - Bittner, Nikolaj; Golez, Denis; Eckstein, Martin; Werner, Philipp (Physical Review B, 2020)
We theoretically investigate the effects of spin frustration on the nonequilibrium dynamics of photoexcited carriers in a half-filled two-dimensional Hubbard model. Using a nonequilibrium generalization of the dynamical cluster approximation, we compare the relaxation dynamics in lattices which interpolate between the triangular lattice and square lattice configuration. To clarify the influence of the density of states of the different lattices, we also consider the corresponding single-site dynamical mean-field theory results. Our study shows that the cooling effect resulting from the disordering of the spin background is less effective in the triangular case because of the frustration. This manifests itself in a longer relaxation time of the photodoped population, as measured by the time-resolved photoemission signal, and a higher effective temperature of the photodoped carriers in the nonthermal steady state after the intra-Hubbard-band thermalization.
CRIS-Team WoS Importer:2021-01-22